(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Recognition of Prior Learning (RPL) is often considered from the perspective of its various potential beneficiaries, including applicants to university and other educational institutions, trade union members and employees, and businesses and enterprises, among others. RPL is said to be about access, transfer, advance, and validation, as it enables lifelong learning, including through the re-skilling and upskilling of the workforce. RPL is also, at its core, a pedagogy in itself, and thus, as many have argued, is ultimately about social justice. While all these views of RPL are indeed accurate, this article is concerned with the use of RPL in the higher education context. We argue that RPL can have an important role in providing personalized learning through tailored trajectories, and also serve to improve curricular relevance. The article highlights the many ways in which RPL intersects with the Funds of Knowledge (FoK) theory, an approach developed in the US in the 1980s, by educators seeking to avoid ’the deficit model’ in relation to their Chicano students. In short, FoK are defined as “all rural and urban skills, experience, technical knowledge of habitat, and the full inventory of social knowledge that households have developed for survival” (p. 253). Identifying these ‘funds’—in other words, employing RPL— can assist with curriculum design, bringing context and relevance (Llopart & Esteban-Guitart, 2017), and enriching the curriculum. Importantly, the approach highlights Learning Incomes, in addition to the usual focus on learning outcomes, bringing the potential of each learner forward. Moreover, FoK (RPL) can restore the learners’ confidence and selfesteem, turning the Higher Education Institution into a source of empowerment